Identification of Chemical Constituents in Ethanolic Extract of Hibiscus sabdariffa L. Calyces (Roselle) by FTIR and GC-MS: Preliminary Phytochemical Screening - Rohani, Siti; Martha, Fadhil Rizki; Astri, Yesi; Putria, Sinta Julia Liona (Fakultas Kedokteran Universitas Sriwijaya, 2025)
Indonesia is widely recognized for its rich biodiversity, which has long served as a valuable resource for traditional herbal medicine. In recent years, interest in plant-based therapies has grown significantly. One such plant, Hibiscus sabdariffa L., commonly known as Rosella, is valued for its therapeutic properties. These benefits arise from the combined effects of its bioactive compounds, allowing it to address a range of health issues. Research has shown that Rosella contains notable levels of flavonoids, saponins, tannins, and alkaloids—all of which contribute to its antibacterial activity. Techniques such as Fourier-transform infrared (FTIR) spectroscopy and gas chromatography–mass spectrometry (GC-MS) are employed to identify these chemical constituents. FTIR analysis has detected functional groups like amines, fatty acids, aldehydes, carboxylic acids, and aromatic rings. Additionally, GC-MS results have indicated the presence of major compounds belonging to the methyl ester group. Noteworthy identified substances include Hexadecanoic Acid Methyl Ester, Hexadecanoic Acid Ethyl Ester, and Benzenepropanoic Acid, 3,5-Bis(1,1-Dimethylethyl)-4-Hydroxy-, Methyl Ester. A review of existing prior research suggests that these compound groups exhibit significant pharmacological potential, including the usage for antioxidant, anticancer, antibacterial, antidiabetic, and anti-inflammatory effects.